Inclusão Digital e protagonismo juvenil: um estudo em dois centros de tecnologia comunitária - Lima, Ana Maria Moraes de Albuquerque (2005)
The present study aimed in identifying operational indicators of Young Activist Network project involving two groups of children ages 9 to 12 years old; the groups Young Activist and the Juventude Ativa. This study is part of an educational program that uses digital applied-technology as tool for developing events related to youth activism. This research was conducted in the community-based technology centers Juventude Interativa Social Lab and Telecentro Padre Joseph Alan Black located at Jardim Antartica in the north side of Sao Paulo city. This study is a qualitative research that uses the action research metodology (Hart). The proposed work approached digital inclusion as a mean to achieve social inclusion while attempts to overcome the digital gap on the fluency of the computer language and knowledge in building community-assets. Juventude Ativa group developed a workshop based on citizenship and environmental education and the Young Activist workshop had the foundation of Roger Hart s participation, theory of technological fluency (Resnick), citizenship (Pina) and other categories related from social aspects that emerged from Vygostky´s scope. Data collected were qualitative only, which were analyzed in two categories as follows; the Pina procedure for citizenship and Hart s participation and technological fluency with Resnick procedure. Our results support the development of youth activism actions using different models/focus. The action research cycle and the development of youth activism mediated by the use of digital technology was not developed in the Environmental Education Workshop by the Juventude Ativa group, but it was developed at the Young Activist Network Workshop using bottom-up model. Although, there was an obvious gain in their learning process using digital technology, the lack of technological fluency still exists causing a gap, which was well noticed in both workshops/ community technology centers.